2016
DOI: 10.1007/978-3-319-49616-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Embodied Team Play, a Distributed Interactive Pong Playground

Abstract: This paper presents work in the field of distributed exertion games, which are controlled by moving the body. People play these games together while being located at different places in the world. The novel contribution of this paper is the introduction of distributed team play in which both collocated and distributed players participate. In our Distributed Interactive Pong Playground (DIPP) players bounce a ball towards a goal by moving, walking, and running around in a 5.3 by 5.3 m interactive playground. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several interactive floor systems exist for indoor purposes, with mainly LEDs or projections as means of feedback, and using either RFID [135], pressure sensors [42,136,137], a laserscanner [58], Doppler radars [136], and/or computer vision to track people [60,138,139]. Several target groups have participated in studies with these floors, including children [140], families [135], students [26,139,141], intellectually disabled people [137], rehabilitants [42], and hearing impaired people [138].…”
Section: Interactive Screen Environmentsmentioning
confidence: 99%
“…Several interactive floor systems exist for indoor purposes, with mainly LEDs or projections as means of feedback, and using either RFID [135], pressure sensors [42,136,137], a laserscanner [58], Doppler radars [136], and/or computer vision to track people [60,138,139]. Several target groups have participated in studies with these floors, including children [140], families [135], students [26,139,141], intellectually disabled people [137], rehabilitants [42], and hearing impaired people [138].…”
Section: Interactive Screen Environmentsmentioning
confidence: 99%
“…It can also be used to change how players interact with each other. In Chapter 4 we already showed that playgrounds can increase coordination by adding (changed) game objects [256], and in Chapter 5 we showed it can balance the game for players' skill differences, or influence with whom players interact [260]. These kinds of steering behavior can be clearly relevant for the goals that are often used as argumentation for interactive play, especially when integrated as adaptable or adaptive elements of the game.…”
Section: Steering Behavior During Embodied Playmentioning
confidence: 99%
“…Several target groups have participated in studies with these floors, including children [281], families [117], students [156,256,260], intellectually disabled people [283], rehabilitants [257], and hearing impaired people [102].…”
Section: Interactive Screen Environmentsmentioning
confidence: 99%
See 2 more Smart Citations